2020
DOI: 10.1098/rsos.191214
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients recycle and the growth of Scenedesmus obliquus in synthetic wastewater under different sodium carbonate concentrations

Abstract: This study illustrated the growth of Scenedesmus obliquus and recycle of nutrients in wastewater combined with inorganic carbon under autotrophic conditions. Scenedesmus obliquus was cultivated under different conditions by adding sodium carbonate (Na 2 CO 3 ) at 15–40 mg l −1 separately in wastewater containing high nitrogen and phosphorus content. The growth characteristics of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It indicated that hormesis mechanism would be triggered in M. aeruginosa and ARGs abundance when the GO presents. The presence of GO at finite concentration in aquatic environment can aggravate the harm of M. aeruginosa and spread of ARGs (Duan et al 2020.…”
Section: Analysis Of Interactions From Metabolomic Aspectsmentioning
confidence: 99%
“…It indicated that hormesis mechanism would be triggered in M. aeruginosa and ARGs abundance when the GO presents. The presence of GO at finite concentration in aquatic environment can aggravate the harm of M. aeruginosa and spread of ARGs (Duan et al 2020.…”
Section: Analysis Of Interactions From Metabolomic Aspectsmentioning
confidence: 99%
“…4,7 Several microalgae species have been reported to have the capability for CO 2 fixation and also to grow in urban wastewaters among which Scenedesmus obliquus and Chlorella vulgaris are the most promising candidates. [8][9][10][11][12] Su et al 13 compared the nutrient removal efficiency of high-potential microalgae species C. vulgaris and Scenedesmus rubescens cultivated in secondary effluent urban wastewater, and reported nitrogen (N) and phosphorus (P) removal efficiencies of >99% for both microalgae species. Liu et al 14 evaluated the influence of CO 2 concentration from 1% to 20% on C. vulgaris in domestic wastewater, and determined a maximum microalgal biomass concentration of 1.12 g L −1 with 10% CO 2 as feed gas.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, chemical absorption of CO 2 has been considered in the past, which involves the addition of solvents like carbonates and amines. Duan et al [ 17 ], cultivated Scenedesmus obliquus in wastewater and obtained an increase in lipid content (from 16 to 25%) as well as biomass concentration (from ~ 0.13 to 0.21 g L −1 ) upon adding 20 mg L −1 sodium carbonate to the wastewater. Enhanced protein (67.1 mg L −1 d −1 ) and lipid (46.9 mg L −1 d −1 ) productivity were obtained by adding monoethanolamine during the fed-batch cultivation of Chlorella fusca LEB 111 although the biomass productivity was found to be similar to the control [ 18 ].…”
Section: Introductionmentioning
confidence: 99%